Surgical outcomes and over one-year follow-up results of laparoscopic Nissen fundoplication for gastroesophageal reflux disease: Single-center experiences - Tae-Gyun Lee; In-Seob Lee; Beom-Su Kim; Hwoon-Yong Jung; Youn-Baik Choi (Asian Journal of Surgery, 2019)
Summary: Background: Laparoscopic antireflux surgery is a standard surgical treatment method for gastroesophageal reflux disease (GERD) in Western countries. However, the procedure has not been actively carried out in Korea because of concerns regarding surgical complications. Here, we conducted this study to evaluate short-term surgical outcomes of laparoscopic Nissen fundoplication (LNF) performed at a single institution. Methods: From January 2010 to August 2016, totally 29 patients underwent LNF for GERD performed by three surgeons at Asan Medical Center, Korea. All patients participated in a telephonic survey including the presence of symptoms and the status of quality of life (QOL). Results: The median age at operation and BMI were 54 years and 23.8 kg/m2, respectively. Preoperatively, 27 patients (93.1%) underwent PPI therapy. All patients had typical or atypical GERD symptoms. One patient (3.4%) required reoperation because of total gastroesophageal junction obstruction. 24 patients (82.8%) reported complete or partial resolution of symptoms, whereas 21 (72.4%) reported partial or complete improvement in quality of life. In patients with reflux esophagitis, GERD symptoms were significantly relieved after LNF (P = 0.005). LNF responders tended to perceive an improvement in quality of life post operation (P < 0.001). Conclusion: LNF is a feasible, safe, and effective treatment option for controlling GERD symptoms as well as improving the quality of life. Presence of reflux esophagitis was a predictor of successful outcomes. Keywords: Antireflux surgery, Gastroesophageal reflux disease, Laparoscopic Nissen fundoplication, Reflux esophagitis